Historical changes in hydrology, geomorphology, and floodplain vegetation of the Willamette River, Oregon. (28th August 2019) - Gregory, Stan; Wildman, Randall; Hulse, David; Ashkenas, Linda; Boyer, Kathryn
Abstract: Historical trends in hydrology, geomorphology, and floodplain vegetation provide fundamental contexts for designing future management of large rivers, an area of fluvial research extensively informed by studies of historical channel dynamics. Changes in hydrology, channel structure, floodplain forests, and large wood were documented for the 273‐km main stem of the Willamette River from 1850 to present. Reduced sediment supply and frequency and magnitude of floods have decreased channel mobility and incised channels, leading to fewer gravel bars, islands, and side channels. Human alteration of channel morphology, vegetation, and bank hardening has exacerbated channel simplification caused by reductions in floods, sediment supply, and inputs of wood. A substantial number of floodplain channels reoccupied remnants of previous active channels inundated during recent floods, demonstrating functional but often forgotten role of historical geomorphic structure in modern floodplains and flood processes. In most reaches, area of floodplain forests in 1990 was only 10% to 25% of the area of forests in 1850. Abundance of wood in the wetted channel was generally greater in reaches with higher abundances of floodplain forests. Future trajectories will be influenced by legacies of the historical river but increasingly will reflect evolution of a new river shaped by human development, changing climate, and emerging hydrogeomorphic and vegetation processes. Understanding historical characteristics and anticipating future rates and patterns of ecosystem change provide fundamental contexts for restoring biophysical processes and structure in a large floodplain river.